2004
DOI: 10.1242/dev.01434
|View full text |Cite
|
Sign up to set email alerts
|

Fat facets and Liquid facets promote Delta endocytosis and Delta signaling in the signaling cells

Abstract: Endocytosis modulates the Notch signaling pathway in both the signaling and receiving cells. One recent hypothesis is that endocytosis of the ligand Delta by the signaling cells is essential for Notch activation in the receiving cells. Here, we present evidence in strong support of this model. We show that in the developing Drosophila eye Fat facets (Faf), a deubiquitinating enzyme, and its substrate Liquid facets (Lqf), an endocytic epsin, promote Delta internalization and Delta signaling in the signaling cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
193
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(206 citation statements)
references
References 61 publications
9
193
0
4
Order By: Relevance
“…A pool of epsin bound to a ubiquitinated cargo may be recruited to clathrincoated pits, for example, by EH domain endocytic proteins, but then dissociate from Ub, thus allowing other interactions of such cargo with coat components. Interestingly, a recent study demonstrated that epsin is critically needed for the function of the Notch receptor Delta (18,19), and that this function involves not only the ubiquitination of Delta and its endocytosis, but also the targeting of internalized Delta to a specific endosomal subcompartment (19). Perhaps, epsin functions to recruit to clathrincoated pits and a recycling endosomal compartment, a pool of ubiquitinated Delta that is otherwise internalized and targeted to lysosomes through a clathrin-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pool of epsin bound to a ubiquitinated cargo may be recruited to clathrincoated pits, for example, by EH domain endocytic proteins, but then dissociate from Ub, thus allowing other interactions of such cargo with coat components. Interestingly, a recent study demonstrated that epsin is critically needed for the function of the Notch receptor Delta (18,19), and that this function involves not only the ubiquitination of Delta and its endocytosis, but also the targeting of internalized Delta to a specific endosomal subcompartment (19). Perhaps, epsin functions to recruit to clathrincoated pits and a recycling endosomal compartment, a pool of ubiquitinated Delta that is otherwise internalized and targeted to lysosomes through a clathrin-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction, which occurs constitutively and is further stimulated by growth factors (6), inhibits the property of epsin to interact with the clathrin coat and the membrane (15). The importance of Ub metabolism in epsin function is further supported by genetic studies in Drosophila (16)(17)(18)(19). The presence in epsin of binding sites for both Ub and core components of the clathrin coat, together with the localization of epsin at clathrin-coated pits, suggested that a function of this protein is to recruit ubiquitinated cargo to clathrin-coated pits, thus triggering its internalization (13).…”
mentioning
confidence: 99%
“…The Drosophila DUB Fat Facets (Faf) (USP9X in humans) interacts directly with the epsin homolog Liquid facets (Laf). Deubiquitylation of Laf by Faf is proposed to facilitate Notch signaling by promoting the internalization of the Notch ligand Delta during fly development (192).…”
Section: Influence On Cell Physiology Through Control Of Receptmentioning
confidence: 99%
“…In Dictyostelium, epsin is dispensable for clathrin-mediated endocytosis (11). In Drosophila, the only epsin ortholog, liquid facets, was shown to have a critical role in the Notch signaling pathway most likely via a specific endocytic function in Notch ligands expressing cells (12)(13)(14)(15). Activation of Notch critically requires its proteolytic cleavage, which is triggered by the transendocytosis of Notch receptors by Notch ligands (16)(17)(18), an action that depends on ubiquitination of these latter proteins (19).…”
mentioning
confidence: 99%